Improving Writing Creativity and Creative Thinking Through Collaborative Guided Writing Strategies Assisted by Gen-AI and Multimedia - Meliyawati; Ade Hikmat; Herri Mulyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The majority of high school students still experience difficulties in creative thinking and creative writing. This study aims to investigate the impact of a guided writing strategy based on Gen-AI and multimedia on creative writing skills and creative thinking abilities. The research method used in this study was a quasi-experimental study involving 250 high school students. Data collection methods used the Torrance Creative Thinking Test and a writing creativity scale. The results showed that a guided writing strategy based on Gen-AI and multimedia improved creative thinking skills and writing creativity in short story writing. Increased flexibility was seen in language variations and adaptation of short stories to short story composition topics. Increased originality was seen in students' thought patterns in the short stories they wrote. Increased elaboration was characterized by more complex and varied linguistic abilities. Furthermore, increased sensitivity was seen in the adaptation of short stories to more comprehensive themes. Thus, a guided writing strategy based on Gen-AI and multimedia can improve thinking skills and writing creativity in short story writing. This study implies that the integration of guided writing with technology can improve writing skills and motivation as well as creative thinking.